Analysis of the endocrine pancreas in adulthood in rats born with intrauterine growth restriction (Research, Society and Development, 2025)
Uncontrolled maternal hyperglycemia can negatively program fetal development, resulting in growth restriction and increased risk of metabolic diseases in adulthood. Severe diabetes (uncontrolled) was induced by streptozotocin (a beta-cytotoxic drug) as a model to cause fetal growth restriction. The aim of this study was to evaluate the functional characteristics of the pancreatic islets of these adult SGA rats at the end of pregnancy, to understand the role of major endocrine–pancreatic hormones in reproductive dysfunctions. For this purpose, non-diabetic and severely diabetic Sprague Dawley rats were used to obtain female offspring (F1), which were classified as appropriate (AGA) or small (SGA) for gestational age, generating two groups: AGA from non-diabetic mothers (Control) and SGA from severely diabetic mothers (SGA group) (n = 10 animals/group. No differences were observed in insulin-, glucagon-, proliferation-, or apoptosis-positive cells. Decompensated maternal diabetes led to intrauterine growth restriction in the offspring and is associated with glucose intolerance, hyperinsulinemia, and oxidative stress in adult females. Although no significant changes were observed in the proportion of insulin-positive cells, the increase in somatostatin-immunoreactive cells suggests that glycemic dysfunction may involve alterations in non-β cells, affecting insulin signaling and secretion. These findings highlight the need for further studies to explore the cellular mechanisms involved in this process.